Literature Review Of M-Banking Experience In Generation X, Y, And Z: Study Of Antecedents And Outcomes - Septiana Iswani (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
Customers are using mobile banking (M-Banking) as a handy way to manage their funds as the world gets more digital. Banking industry aim to provide customers a great experience across M-Banking channel to attract more customer, sustain their customer’s loyalty, and get higher revenue for the continuous usage in the future. In order to investigate the design of a customer experience from a holistic standpoint, this study expand on the literature that has already been written on the topic and give an overview of it in this paper. Understanding consumer behavior thus requires examination of the various patterns of personality traits and their impact over generations. This study also explains the comprehend of inter-generational relationship through their behavioral biases across generational cohorts. Few papers are examined through 12 journal articles published between 2008 and 2023 in top journal. The findings indicate that the customer experience is dynamic and proposed a broaden model to examine such as S-O-R framework to get better understanding. M-Banking experience’s antecedent and outcomes among generation X,Y, and Z is also approached such as how and to what extent an experience influence loyalty and continuous usage intention. In each of this area, this study identifies and discuss important issues worthy for further research.